Inflammation-related collagen fibril destruction contributes to temporomandibular joint disc displacement via NF-κB activation - Shengjie Cui; Yanning Guo; Yu Fu; Ting Zhang; Jieni Zhang; Yehua Gan; Yanheng Zhou; Yan Gu; Eileen Gentleman; Yan Liu; Xuedong Wang (International Journal of Oral Science)
Abstract Temporomandibular joint (TMJ) disc displacement is one of the most significant subtypes of temporomandibular joint disorders, but its etiology and mechanism are poorly understood. In this study, we elucidated the mechanisms by which destruction of inflamed collagen fibrils induces alterations in the mechanical properties and positioning of the TMJ disc. By constructing a rat model of TMJ arthritis, we observed anteriorly dislocated TMJ discs with aggravated deformity in vivo from five weeks to six months after a local injection of Freund’s complete adjuvant. By mimicking inflammatory conditions with interleukin-1 beta in vitro, we observed enhanced expression of collagen-synthesis markers in primary TMJ disc cells cultured in a conventional two-dimensional environment. In contrast, three-dimensional (3D)-cultivated disc cell sheets demonstrated the disordered assembly of inflamed collagen fibrils, inappropriate arrangement, and decreased Young’s modulus. Mechanistically, inflammation-related activation of the nuclear factor kappa-B (NF-κB) pathway occurs during the progression of TMJ arthritis. NF-κB inhibition reduced the collagen fibril destruction in the inflamed disc cell sheets in vitro, and early NF-κB blockade alleviated collagen degeneration and dislocation of the TMJ discs in vivo. Therefore, the NF-κB pathway participates in the collagen remodeling in inflamed TMJ discs, offering a potential therapeutic target for disc displacement.